The Influence of Digital Marketing Through Social Media and Environmental Awareness on the Purchase Decision of Thrifting Products Among Students in Malang City - Marianus Jaban; Moch Nurhidayat; Imam Hidayat (International Research and Development for Human Beings (IRDH), 2026)
The growing trend of thrifting among college students is influenced not only by economic factors but also by the intensity of digital promotions and increasing awareness of environmental sustainability issues. This study aims to analyze the influence of digital marketing via social media on purchasing decisions, the influence of environmental awareness on purchasing decisions, as well as the simultaneous influence of these two variables. The study employs a quantitative approach using explanatory research methodology. The study finds that digital marketing via social media and environmental awareness both have a positive and significant influence on students’ decisions to purchase thrifted prod-ucts in Malang. Digital marketing, through quality content, consistent promotion, and ac-tive interaction, effectively increases interest and purchasing decisions, while environmental awareness motivates students to choose thrifted products as a sustainable alternative that reduces textile waste. Together, these factors strongly shape purchasing behavior, with digital marketing acting as an external driver and environmental awareness as an in-ternal motivator. Although other elements such as price, quality, lifestyle, and social in-fluence also play roles, the combined impact of digital marketing and environmental awareness is substantial. Overall, the research confirms that effective marketing strategies and efforts to raise environmental consciousness are key to promoting sustainable con-sumption among students